Complement Activation During Ischemia/Reperfusion Injury Induces Pericyte-to-Myofibroblast Transdifferentiation Regulating Peritubular Capillary Lumen Reduction Through pERK Signaling - Giuseppe Castellano; Rossana Franzin; Alessandra Stasi; Chiara Divella; Fabio Sallustio; Fabio Sallustio; Paola Pontrelli; Giuseppe Lucarelli; Michele Battaglia; Francesco Staffieri; Antonio Crovace; Giovanni Stallone; et al. (Frontiers in Immunology, 2018)
Pericytes are one of the principal sources of scar-forming myofibroblasts in chronic kidneys disease. However, the modulation of pericyte-to-myofibroblast transdifferentiation (PMT) in the early phases of acute kidney injury is poorly understood. Here, we investigated the role of complement in inducing PMT after transplantation. Using a swine model of renal ischemia/reperfusion (I/R) injury, we found the occurrence of PMT after 24 h of I/R injury as demonstrated by reduction of PDGFRβ+/NG2+ cells with increase in myofibroblasts marker αSMA. In addition, PMT was associated with significant reduction in peritubular capillary luminal diameter. Treatment by C1-inhibitor (C1-INH) significantly preserved the phenotype of pericytes maintaining microvascular density and capillary lumen area at tubulointerstitial level. In vitro, C5a transdifferentiated human pericytes in myofibroblasts, with increased αSMA expression in stress fibers, collagen I production, and decreased antifibrotic protein Id2. The C5a-induced PMT was driven by extracellular signal-regulated kinases phosphorylation leading to increase in collagen I release that required both non-canonical and canonical TGFβ pathways. These results showed that pericytes are a pivotal target of complement activation leading to a profibrotic maladaptive cellular response. Our studies suggest that C1-INH may be a potential therapeutic strategy to counteract the development of PMT and capillary lumen reduction in I/R injury.